2015
DOI: 10.1007/s00018-015-1976-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits BAFF-stimulated cell proliferation and survival by suppressing mTOR-mediated PP2A-Erk1/2 signaling pathway in normal and neoplastic B-lymphoid cells

Abstract: B-cell activating factor (BAFF) is involved in not only physiology of normal B cells, but also pathophysiology of aggressive B cells related to malignant and autoimmune diseases. Rapamycin, a lipophilic macrolide antibiotic, has recently shown to be effective in the treatment of human lupus erythematosus. However, how rapamycin inhibits BAFF-stimulated B-cell proliferation and survival has not been fully elucidated. Here, we show that rapamycin inhibited human soluble BAFF (hsBAFF)-induced cell proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 61 publications
(123 reference statements)
0
40
0
1
Order By: Relevance
“…A series of data have uncovered that BAFF acts as a crucial factor in aggressive B-cell malignancies and various autoimmune diseases, such as SLE, RA and SS [13, 21, 41, 46, 47]. For example, lupus serum contains elevated levels of BAFF [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of data have uncovered that BAFF acts as a crucial factor in aggressive B-cell malignancies and various autoimmune diseases, such as SLE, RA and SS [13, 21, 41, 46, 47]. For example, lupus serum contains elevated levels of BAFF [48].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently revealed that hsBAFF enhances cell proliferation/viability in Erk1/2-dependent manner in normal and neoplastic B-lymphoid cells [40, 41]. Moreover, hsBAFF also augments proliferation/survival in the cells, at least in part, through activating mTOR-mediated S6K1 and 4E-BP1 pathways [41, 42]. Here, we identified that IL-2, IL-4, IFN-γ or TNF-α reinforced hsBAFF-stimulated B-cell viability/survival by activating both Erk1/2 and S6K1 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF has been identified as a promoter of mTOR activation [33]. In B cells, rapamycin was able to block BAFF-stimulated mTOR activation, inhibit proliferation, and induce apoptosis [33, 34]. …”
Section: Immune Systemmentioning
confidence: 99%
“…Protein phosphatase 2A (PP2A) is a ubiquitous enzyme that promotes basal phosphatase activity to serve as a negative regulator of cell growth and division (51,52). The 14-3-3 family of highly conserved proteins bind to phosphorylated serine or threonine peptides to regulate cell growth and metabolic processes (53).…”
Section: Discussionmentioning
confidence: 99%